The effect of low-intensity exercise duration on acute skeletal muscle signalling responses - Harrison, P.; Dugdale, H.; Hulston, C.; Martin, N.; Bailey, S.; Bishop, D.; Ferguson, R. (Journal of Science and Cycling, 2024)
Introduction Elite endurance athletes typically demonstrate a polarised or pyramidal training intensity distribution, comprising of large volumes of low-intensity training (70-90%) and smaller volumes of moderate- and high-intensity training (10-30%) (Stöggl & Sperlich, 2015). Considerable research has investigated high-intensity training optimisation (Laursen & Buchheit, 2019), however, there is limited research identifying best practice for manipulating the duration and frequency of low- intensity training sessions.